Performance evaluation of Invariant moment features on Image retrieval - Kumar, Ravinder; Kumar Singh, Brajesh (International Journal of Computer Sciences and Engineering, 2025)
Now a day the database is increases into hues size of database in multimedia and internet technology, so data science and content Based Image Retrieval (CBIR) system is an important research area since last few years. There are so many models of CBIR have been proposed by various author to retrieve images from huge database. In this work, we present a CBIR system using HU’s seven Invariant moment feature and measures the performance of system in MATLAB. The similarity between query image and database image is measure by Euclidian distance method and the efficiency of system is measure by calculating the precision and recall. All the experimental results are performed on five different standard datasets on 450 images.